2003
DOI: 10.1046/j.1365-2141.2003.04119.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of thrombotic thrombocytopenic purpura based on modulation by patient plasma of normal platelet adhesion under flow condition

Abstract: Summary. We have designed a simple test for the early diagnosis and treatment monitoring of thrombotic thrombocytopenic purpura (TTP). We examined plasma from 24 TTP patients and normal plasma using a cone and plate(let) analyser (CPA). Test plasma was mixed with citrated normal whole blood (group O) and subjected to flow at a shear rate of 1800/s. Mixing normal plasma (12AE5, 25, 50 or 75 ll) with heterologous normal whole blood (final volume of 200 ll) resulted in a decrease of surface coverage (SC, maximall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Plasma of patients with other thrombocytopenic entities including hemolytic uremic syndrome did not change the platelet deposition [27]. In another yet not published study we found a reverse correlation between the increased normal platelet adhesion under shear condition (2050 s -1 ) caused by acute TTP plasma and ADAMTS-13 activity measured by collagen-binding assay.…”
Section: Testing Ulvwf Multimers and Adamts-13 Activitysupporting
confidence: 52%
“…Plasma of patients with other thrombocytopenic entities including hemolytic uremic syndrome did not change the platelet deposition [27]. In another yet not published study we found a reverse correlation between the increased normal platelet adhesion under shear condition (2050 s -1 ) caused by acute TTP plasma and ADAMTS-13 activity measured by collagen-binding assay.…”
Section: Testing Ulvwf Multimers and Adamts-13 Activitysupporting
confidence: 52%
“…In the FRETS‐VWF73 assay, cleavage is enabled by the use of a short peptide substrate, whereas in the VWF multimer and CB assays, a denaturing agent is used to expose the cleavage site in full‐length VWF. To circumvent the potential pitfalls of such assays, various shear‐based systems for determining ADAMTS‐13 activity have been developed . In one such study, the presence of inhibitors was qualitatively assessed with a shear assay, and the results obtained were largely consistent with those of the FRETS‐VWF73 assay .…”
Section: Introductionmentioning
confidence: 99%
“…First, Shenkman et al [18] evaluated the ability of TTP plasma to increase the platelet deposition on a polystyrene surface from normal plasma under flow conditions using a cone and plate(let) analyzer (CPA) method. Second, we recently described that ULVWF multimers, upon release, form extremely long and platelet-decorated string-like structures on the surface of endothelial cells under fluid shear stress [19].…”
Section: Introductionmentioning
confidence: 99%